University Teachers’ Intercultural Profiles and Their Own Positionings towards Intercultural Language Teaching and Learning of English - Muhammad Aulia; Teguh Khaerudin (Proceedings of AICS - Social Sciences, 2021)
The intercultural approach to English language teaching and learning has been taught and implemented in Indonesian universities in multiple names: intercultural communication, intercultural pedagogy, and others. In essence, intercultural values are promoted and inculcated into Indonesian learners of English. However, the pedagogy itself can be interpreted diversely across individuals and contexts. The present study strives to reveal the interrelationship between teacher personal development and teacher belief in shaping one’s intercultural profile positioning. This is vital for understanding the real implementation of the intercultural pedagogy in English as a Foreign Language (EFL) teaching setting. As a qualitative exploratory case study, this study interviewed six teachers of three universities in Indonesia. Their voices were extracted and analyzed to understand the teachers’ positionings related to intercultural EFL pedagogy. The qualitative data analysis identified some themes related to the individual teacher beliefs, which emphasized resistance, contradiction, and ambivalence as intercultural EFL teachers. The present study highlights these intercultural profiles and emphasizes the importance of understanding EFL teachers’ intercultural positioning to improve the quality of the intercultural pedagogy. The intercultural approach to EFL teaching and learning is known to be highly personal, contextual, and dynamic. Understanding the formation of teacher identity and awareness of the sociocultural relations in EFL teaching contexts should be a matter of concern for future research and EFL teacher professional development.Keywords: intercultural pedagogy, teacher education, Indonesian universities, and intercultural profiles.